The Effect of Compensation, Organizational Commitment, and Job Satisfaction on Turnover Intention at Bank XYZ - Kusuma, Alvian Guntur Perdana; Febrina, Rima (Universitas Pamulang, 2023)
This study aims to determine and examine the effect of Compensation, Organizational Commitment, and Job Satisfaction on Turnover Intention at BANK XYZ. Sampling in this study was carried out by census or saturated samples. The number of samples taken in this study were 67 employees of BANK XYZ. The data were obtained from the results of distributing questionnaires and the analytical method used was multiple regression with the help of the SPSS version 23 program. The results showed that the variable job satisfaction partially did not affect employee job satisfaction, but organizational commitment and compensation had an effect on employee turnover intention. However, overall the independent variables together have a significant influence on turnover intention at BANK XYZ.